Improving relevance in B2B research: analysis and recommendations. Issue 7 (29th July 2014) - Brennan, Ross; Tzempelikos, Nektarios; Wilson, Jonathan
Abstract : Purpose: – The purpose of the study is to identify and discuss critical aspects of the academic/practitioner gap and suggest how to make marketing research more relevant. Design/Methodology/Approach: – The study uses data from an earlier study of eight qualitative interviews conducted with business-to-business (B2B) marketing practitioners and from an earlier quantitative study among 128 academics and 510 marketing research practitioners. The data are re-analyzed for this article. Findings: – Results show that academics and practitioners agree that academic research should be of more practical value. However, their priorities differ. For academics, publishing in refereed journals is the first priority and influencing practice is of much lower priority, while practitioners are not interested in the methodological and theoretical advances of marketing research; their priority is to satisfy day-to-day practical needs. Hence, practitioners have no interest in academic journals. The academic reward system tends to reinforce this divide because academic career progression depends substantially on the production of refereed journal articles. Research limitations/implications: – Much prior consideration has been given to how academic journals can be made more relevant to practitioners, which is a desirable goal. However, a more fruitful approach for B2B academics would be to embrace new technologies such as blogging and social media to reach practitioners through their preferred channels. If greater relevance is to be achieved, then consideration needs to be given to the views of doctoral students, and to doctoral training processes in B2B marketing. Practical implications: – The study provides academics with guidance concerning how marketing research can have a greater effect on the practice of marketing. Social implications: – Originality/value: – The study contributes to the research base by identifying and discussing critical aspects of the academic/practitioner gap. The study also offers insights into how managerial relevance in marketing research can, practically, be improved.